Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.93
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Constraint-Based Behavior in Neural Models via Targeted Fine-Tuning

Abstract: A growing body of literature has focused on detailing the linguistic knowledge embedded in large, pretrained language models. Existing work has shown that non-linguistic biases in models can drive model behavior away from linguistic generalizations. We hypothesized that competing linguistic processes within a language, rather than just non-linguistic model biases, could obscure underlying linguistic knowledge. We tested this claim by exploring a single phenomenon in four languages: English, Chinese, Spanish, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…1 Within work in natural language processing, existing models have been claimed to capture aspects of Principle A (e.g., Warstadt et al, 2020;Hu et al, 2020). Principle C has received less attention, though see Mitchell et al (2019) which found that LSTM language models failed to obey Principle C. Coreference, more broadly, has also been explored, with results suggesting that models encode features of coreference resolution (e.g., Sorodoc et al, 2020) and the interaction of implicit causality and pronouns (verb biases that influence preferred antecedents for pronouns; Upadhye et al, 2020;Davis and van Schijndel, 2021;Kementchedjhieva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1 Within work in natural language processing, existing models have been claimed to capture aspects of Principle A (e.g., Warstadt et al, 2020;Hu et al, 2020). Principle C has received less attention, though see Mitchell et al (2019) which found that LSTM language models failed to obey Principle C. Coreference, more broadly, has also been explored, with results suggesting that models encode features of coreference resolution (e.g., Sorodoc et al, 2020) and the interaction of implicit causality and pronouns (verb biases that influence preferred antecedents for pronouns; Upadhye et al, 2020;Davis and van Schijndel, 2021;Kementchedjhieva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%